Effects of remote Baduanjin Qigong intervention on quality of life and physical function in patients with mild to moderate Parkinson’s disease: a protocol of randomized controlled trial - Yu, Jizhe; Jia, Yi; Ma, Guanglin; Wang, Dong; Zhang, Zhen; An, Zengbao; Li, Yingkui (Frontiers in Neurology, 2025)
BackgroundThis study aims to evaluate the effects of remote Baduanjin Qigong intervention on the quality of life and physical function in patients with mild to moderate Parkinson’s disease (PD) through a randomized controlled trial (RCT) and to compare its efficacy with conventional exercise rehabilitation.Methods/designThis RCT will enroll participants who, following baseline assessments and physical function tests, will be randomly allocated into one of three groups: the Qigong group (QG), the conventional exercise rehabilitation group (EG), or the control group (CG). The QG will engage in live-streamed Baduanjin (Eight-Section Brocade) sessions three times per week, each lasting 40 min, with additional self-practice encouraged. The EG will undergo a structured regimen consisting of moderate period high-intensity resistance training (MP-HI-RT) combined with moderate period low-intensity aerobic exercise (MP-LI-AE), also performed remotely in three 40-min sessions per week. The CG will continue their routine daily activities without additional exercise intervention. Outcome assessments will be conducted at baseline (Week 1), mid-intervention (Week 6), and post-intervention (Week 12) to evaluate both short-term and long-term effects. The primary outcomes include quality of life, evaluated using the Parkinson’s Disease Questionnaire-39 (PDQ-39), the MOS 36-item Short Form Health Survey (SF-36), and the Unified Parkinson’s Disease Rating Scale developed by the Movement Disorder Society Part I (MDS-UPDRS Part I). Secondary outcomes encompass reaction time, balance, physical coordination, flexibility, and walking capacity.DiscussionThe importance of exercise rehabilitation for PD is increasingly recognized by doctors and patients. However, accessible and practical rehabilitation methods remain an area of active investigation. Remote Baduanjin Qigong intervention via the Internet offers a promising alternative for mild to moderate Parkinson’s disease patients.Clinical trial registrationhttps://www.chictr.org.cn/bin/project/edit?pid=268557, Identifier ChiCTR2500101461.